Kajian Faktor - Faktor Pendukung Industri Rumahan Bangka Belitung Berbasis AHP - Magdalena, Hilyah; Santoso, Hadi (Faculty of Computer Science, University of Jember, 2023)
This research was conducted in the Bangka Belitung region specifically observing what criteria could support and hinder the development of home industries. The home industry is a small-scale industry generally carried out in the family sphere and is driven by women. Home industries need to receive support from the provincial government to survive and increase the scale of production. To make support for home industries more targeted, this research summarizes several criteria related to the conditions of home industries and the businesses they run. In Bangka Belitung Province, several types of businesses are run on a home industry scale. Based on the condition of the home industry which has multiple criteria and multiple alternatives, this research uses the Analytical Hierarchy Process method and Expert Choice software as data processing aids. The data processing results show that industrial business is the highest alternative with a weight of 24.7% and the highest criterion is strategy at 23.7%. These results indicate that the largest portion of home industry business actors is engaged in the industrial sector and to encourage the progress of the home industry the most important factor is strategy, namely understanding the type of business they are involved in, labor-intensive industries, paying attention to production factors, electricity capacity, and business operations. The next stage is to design a user interface for a web-based system as a means of collecting home industry data.